Analisis Hubungan Procurement pada Manajemen Supply Chain pada PT. Industri Nabati Lestari di Kek Sei Mangke - Anzalna Nur Izatunisa; Nuri Aslami (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This internship journal aims to analyze the relationship between procurement and supply chain management at PT. Sustainable Vegetable Industry in Kek Sei Mangke. The method used in this research is descriptive qualitative with data collection techniques through observation, interviews and documentation studies. The research results show that procurement has an important role in increasing the efficiency of supply chain management in companies. procurement can help in aligning strategy and goals, building good relationships with suppliers, integrating sustainability in the supply chain, diversifying suppliers, and increasing added value in company operations. By doing these things, procurement can help increase efficiency in the company's supply chain management. Therefore, companies need to pay attention to the role of procurement in supply chain management to improve overall company performance.